O-49 What can be learned from hospital interpreters about cultural issues relevant to advance care planning and end-of-life issues ?. (1st September 2015) - Fabri, Anne-Marie; Hayes, B; Coperchini, M; Parkar, R; Austin-Crowe, Z
Abstract : Background: There is a growing body of advance care planning (ACP) research but people from culturally and linguistically diverse (CALD) communities, living in Australia, are largely under-represented. Research evaluating ACP by CALD communities internationally, reports a generally lower uptake, with some barriers identified. Aim: This study builds on an earlier pilot study, and aims to increase understanding of cultural issues relevant to advance care planning and end-of-life decision-making. Methods: Participants in this qualitative study are hospital-employed interpreters from five metropolitan health services, participating in one-to-one semi-structured interviews. Hospital interpreters were expected to have extensive experience of discussions about treatment limitations and end-of-life care, for the cultures that they interpret for. They were also expected to have personal experience of a culture. Interviews explored how people, within the interpreter's language group: discuss death and dying; make decisions about end-of-life care; and respond to ACP discussions To date thirty-one interviews have been completed, in addition to the six pilot interviews, and cover 14 language groups. The interviews have been transcribed and analysed thematically, using open and axial coding. Results: Three major themes arising from the interviews will be discussed: Planners v Non-planners Individual autonomy v Collective good Diversity within cultures Discussion/conclusion: Findings from this study identify considerable diversity in how medical decision-making, and future planning, might be valued by an individual. Autonomy is the pre-eminent ethical principle that underpins ACP, but is not always a  highly regarded value within some cultures. This has implications for how ACP might be understood and made relevant to people from some CALD communities.